2012
DOI: 10.1038/ng.2368
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of widespread selection on standing variation in Europe at height-associated SNPs

Abstract: Strong signatures of positive selection at newly arising genetic variants are well-documented in humans1–8, but this form of selection may not be widespread in recent human evolution9. Because many human traits are highly polygenic and partly determined by common, ancient genetic variation, an alternative model for rapid genetic adaptation has been proposed: weak selection acting on many pre-existing (standing) genetic variants, or polygenic adaptation10–12. By studying height, a classic polygenic trait, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
354
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(381 citation statements)
references
References 33 publications
23
354
2
2
Order By: Relevance
“…Although our findings are suggestive of selection on height, and are in line with genetic evidence regarding past selection on stature in Northern Europe [28], we do not present direct evidence for natural selection. The phenotypic correlation we observe can be caused by both environmental and/or genetic factors, and we can infer the degree of natural selection only to the extent to which genetic effects on both traits correlate [29].…”
Section: Discussionsupporting
confidence: 64%
“…Although our findings are suggestive of selection on height, and are in line with genetic evidence regarding past selection on stature in Northern Europe [28], we do not present direct evidence for natural selection. The phenotypic correlation we observe can be caused by both environmental and/or genetic factors, and we can infer the degree of natural selection only to the extent to which genetic effects on both traits correlate [29].…”
Section: Discussionsupporting
confidence: 64%
“…Concordant with changes in the climate over that time frame, tropical alleles shifted into temperate populations, potentially representing a genetic response to climate change (Umina et al, 2005). In humans, Turchin et al (2012) found strong evidence for selective changes in allele frequencies at hundreds of height-associated loci in European populations. This study illustrates both the potential for such analyses and the massive work required for successful dissection of complex trait variation.…”
Section: Adaptive Evolution and Global Changementioning
confidence: 99%
“…For polygenic quantitative traits (Rockman, 2012), genomic approaches could be used to detect subtle changes at multiple loci of small effect (Hansen et al, 2012;Turchin et al, 2012). Continuing advancements in genomic technologies and bioinformatics will improve our understanding of climatic adaptation in model (Fournier-Level et al, 2011;Hancock et al, 2011) and nonmodel (Allendorf et al, 2010) organisms.…”
Section: Adaptive Evolution and Global Changementioning
confidence: 99%
See 1 more Smart Citation
“…This especially in the view that most traits of ecological importance are likely to be polygenic (Falconer and Mackay, 1996;Hill and Kirkpatrick, 2010;Yang et al, 2010), and thereby likely to be weakly selected at the level of individual loci (Turchin et al, 2012). Hence, it seems possible that the likelihood of parallel genetic differentiation in small populations could decrease with the increasing number of genes coding for a given trait.…”
Section: The Importance Of Selectionmentioning
confidence: 99%